Inclusive Islamic Education Management: Strengthening Religious Moderation in Schools - Moh. Kholip Beril arrahman; Siti Aimah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to analyze the strategy of inclusive Islamic education management in strengthening religious moderation in high schools in Banyuwangi Regency. Using a case study design, this study dissects the orchestration of the five pillars of management: curriculum, leadership, teacher competence, student engagement, and digital mitigation. The findings show that the transformative leadership of school principals is a determinant pillar or "heart" of the organization that synchronizes institutional policies with the local wisdom of "True Brotherhood". The main innovation of this research is the "Participatory Harmony-Based Inclusive Management" model, which introduces the Harmony Audit instrument for real-time detection of latent friction. The results of the intervention showed an increase in students' cognitive resilience scores by 32% and a 30% decrease in exposure to radical narratives through the "narrative immunization" strategy in digital literacy. In addition, the transformation of the teacher's dialogical pedagogy increased the effectiveness of class discussions by 40%, while the engineering of the extracurricular ecosystem successfully mitigated the phenomenon of "voluntary segregation". The theoretical implications confirm that the total integration of managerial authority, cultural intelligence, and digital mitigation is a systemic solution to create a cohesive and resilient school ecosystem in the era of information disruption